2018
DOI: 10.1186/s40561-018-0065-y
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic eye movement metrics for students’ performance assessment

Abstract: This paper reports on the feasibility of using eye tracking as a tool for students' performance assessment in a medical serious game. We are particularly interested in analyzing the relationship between learners' visual behaviour and their performance while solving medical cases. The objective of this study is twofold. First, we analyze how the students visually explore the learning environment across different areas of interest. Second, we examine whether static and dynamic eye tracking metrics can have an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…These results demonstrated that there were no particular AOIs that aroused the most the students' attention. These findings are contradictory with our previous work [2] where the statistical analyses showed the opposite effect in terms of fixation duration. In fact, one-way ANOVAs showed that the S region was the most fixated one over all the medical cases.…”
Section: Engagement Index Distribution Across the Aoiscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that there were no particular AOIs that aroused the most the students' attention. These findings are contradictory with our previous work [2] where the statistical analyses showed the opposite effect in terms of fixation duration. In fact, one-way ANOVAs showed that the S region was the most fixated one over all the medical cases.…”
Section: Engagement Index Distribution Across the Aoiscontrasting
confidence: 99%
“…These results confirm our hypothesis in [2] regarding fixation duration. Indeed it was found that longer fixation duration on specific information areas has Journal of Intelligent Learning Systems and Applications no effect on learners' performance.…”
Section: Engagement Index and Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…The TTFF indicates the amount of time that it takes an individual to look at a specific Area of Interest (AoI) from stimulus onset [22]. TTFF can be thought as early measure of processing [23] and it can provide information about how certain aspects of a visual scene are prioritized, capturing early/uncontrolled attention and hence, indexing interest [24,25].…”
Section: First Fixationmentioning
confidence: 99%
“…An eye tracker was used (Tobii X3-120, Tobii Technology AB, Sweden) in order to track valid responses, ensuring participants initiated their ocular saccade from the fixation cross at the center of the screen, and actually hit the stimulus. The eye tracker further allowed us to collect TTFF, indexing early/uncontrolled attention toward stimuli [25].…”
Section: Procedures and Materialsmentioning
confidence: 99%